2008
DOI: 10.1093/acprof:oso/9780195369670.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Clonality

Abstract: About 99.9% of vertebrate species reproduce sexually. This makes the exceptional 0.1%—the asexual or clonal reproducers—fascinating in their own right, and also uniquely instructive about the biological significance of alternative reproductive modes. This book describes the genetics, ecology, natural history, and evolution of all of the world's approximately 100 “species” of vertebrate animal that routinely display one form or another of clonal or quasi-clonal reproduction. The book investigates the astounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(29 citation statements)
references
References 504 publications
0
29
0
Order By: Relevance
“…Similarly, the duplication of the NOR2 in female Batura toads occurs through a gametogenetic mechanism (premeiotic endomitosis) that is well known from parthenogenetic and hybridogenetic vertebrates [23,45,46]. However, the Batura toad system seems unique among vertebrates in that (i) meiotic processes differ between sexes, and (ii) females simultaneously transmit one genome that is clonally duplicated, and another that undergoes normal meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the duplication of the NOR2 in female Batura toads occurs through a gametogenetic mechanism (premeiotic endomitosis) that is well known from parthenogenetic and hybridogenetic vertebrates [23,45,46]. However, the Batura toad system seems unique among vertebrates in that (i) meiotic processes differ between sexes, and (ii) females simultaneously transmit one genome that is clonally duplicated, and another that undergoes normal meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Polyploid gibel carp, Carassius auratus gibelio, because of the existence of a minor but significant portion of males in natural populations and the discovery of multiple modes of unisexual gynogenesis and sexual reproduction in some gynogenetic clones [23], has been noted extensively [12,24]. Through a series of studies, various gynogenetic clones and the clone-specific genetic markers have been identified, and used to perform studies on the evolutionary and ecological genetics [2533].…”
Section: Discovery Of Multiple Modes Of Unisexual Gynogenesis and Sexmentioning
confidence: 99%
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009).…”
Section: Introductionmentioning
confidence: 99%